“What makes Human Beings into Moral Beings?”1 The Significance of Ethics in the Process of Evolution - Babich, Babette (Voluntas: Revista Internacional de Filosofia, 2011)
Just as animals in general are described as “feeling” nothing like “pain” but “stimuli responses” or “behaviours,” scientific theorists once proposed to reduce the differences between socio-cultural expressions of pain to differences in general between the races: Black, White, Asian, and especially so-called aboriginal peoples and Nazi experiments on human pain extended the same test of pain thresholds from experiments performed on animals for centuries (the same experiments on animals unchecked to this day) to human beings designated as subhuman. Ethological studies by Franz de Waal suggest that animals share this capacity for sympathizing with the other. Schopenhauer’s notion of compassion thus serves as the basis for a new understanding of becoming moral. This essay situates Schopenhauer with respect to Kant as well as Nietszche and develops connections with Levinas and Adorno as well as Isaac Bashevis Singer